2014
DOI: 10.1016/j.actbio.2013.12.057
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of bladder cancer cells from normal urothelial cells with high specificity and sensitivity: Combined application of atomic force microscopy and modulated Raman spectroscopy

Abstract: Atomic force microscopy (AFM) and modulated Raman spectroscopy (MRS) were used to discriminate between living normal human urothelial cells (SV-HUC-1) and bladder tumour cells (MGH-U1) with high specificity and sensitivity. MGH-U1 cells were 1.5-fold smaller, 1.7-fold thicker and 1.4-fold rougher than normal SV-HUC-1 cells. The adhesion energy was 2.6-fold higher in the MGH-U1 cells compared to normal SV-HUC-1 cells, which possibly indicates that bladder tumour cells are more deformable than normal cells. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 47 publications
2
42
0
1
Order By: Relevance
“…This is in a good agreement with a previous study that showed that the cancer cells are significantly thicker than their normal counterparts. 24 MSC cells were significantly thicker than NHOst cells, and their thickness was 4.41 ± 0.65 and 3.17 ± 0.63 μm, respectively. The MSC and NHOst cells were significantly larger than MG-63 cells, while the size of MSC and NHOst cells was not significantly different.…”
Section: Resultsmentioning
confidence: 98%
“…This is in a good agreement with a previous study that showed that the cancer cells are significantly thicker than their normal counterparts. 24 MSC cells were significantly thicker than NHOst cells, and their thickness was 4.41 ± 0.65 and 3.17 ± 0.63 μm, respectively. The MSC and NHOst cells were significantly larger than MG-63 cells, while the size of MSC and NHOst cells was not significantly different.…”
Section: Resultsmentioning
confidence: 98%
“…Recent AFM single-cell experiments (Canetta et al, 2014;Rianna et al, 2015;Simon et al, 2016) have commonly focused on measuring cellular Young's modulus, which is dependent on the cytoskeleton--particularly the actin filaments (Rotsch and Radmacher, 2000). Cellular relaxation, by contrast, is dependent on the cytoplasm (Moeendarbary et al, 2013).…”
Section: Rusults and Discussionmentioning
confidence: 99%
“…However, current studies (Canetta et al, 2014;Rianna et al, 2015) mainly focused on the measurement of cellular Young's modulus, which reflects only the elastic properties of cells. Living cells, which are actually viscoelastic, exhibit heterogeneous rheological behaviors during their life cycles (Moeendarbary et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…27,52 Many studies report the Raman spectroscopic detection of malignant and premalignant tissues in different sites of the body with high sensitivities, has the potential as a new tool in the clinico-oncological practice. 19 The diagnostic potential of Raman spectroscopy has been demonstrated in cancers of various organs including the esophagus, 53 breast, 54 lung, 55 bladder, 56 skin, 57 and prostate. 31 This work described the spectra investigation of single normal and cancerous liver cells using confocal Raman microspectroscopy technology.…”
Section: Discussionmentioning
confidence: 99%